Three-Axis Sensor Development for Ground Reaction Forces Measurement with Sports Applications - Moscoso, R.; Callupe, R.; Garcia, J.; Villota, E.R. (Springer Science and Business Media Deutschland GmbH, 2022)
Pattern analysis of ground reaction forces (GRF) exerted by athletes during sports execution helps coaches design appropriate training to enhance athletes’ performance and prevent injuries. Nevertheless, few portable devices are capable of measuring such plantar forces in 3-axis without restricting the athlete’s movement. This paper presents the electronic design of a wearable plantar outsole for 3-axis GRF measurement suitable for sports applications, with emphasis on the volleyball reception technique. The outsole is composed of five 3-axis force sensors made of piezoresistive sensors. Sensed signals are processed in a microcontroller ESP32 and subsequently transmitted to a mobile phone by Bluetooth where data plots are displayed for immediate analysis. A static test over one foot is performed in order to evaluate the sensor error. Tests of gait analysis and frontal squat are also performed to validate the operation of the data-acquisition system. The 3-axis GRF sensor measures forces up to 1000 N in the z-axis and ±200 N in both x- and y-axis. Thus, the outsole senses up to 5000 N in the z-axis and ±1000 N in the x- and y-axis. Measurement errors were 148 ± 39 N (24 ± 6.3%) and 65 ± 25 N (10 ± 3.9%) in the z-axis, for the static and the frontal squat tests, respectively.
Keywords: 3-axis force sensors; Ground reaction forces; Volleyball; https://purl.org/pe-repo/ocde/ford#3.03.02